2015
DOI: 10.1111/cas.12581
|View full text |Cite
|
Sign up to set email alerts
|

Multitargeting strategy using lenvatinib and golvatinib: Maximizing anti‐angiogenesis activity in a preclinical cancer model

Abstract: Almost all cancers show intrinsic and/or evasive resistance to vascular endothelial growth factor (VEGF) inhibitors by multiple mechanisms. Serum angiopoietin-2 (Ang2) level has been proposed as a potential biomarker of VEGF inhibitor response in several cancers. From these clinical observations, the Ang2 and Tie2 (its receptor) axis has been focused on as a promising target. Here, we show a novel strategy to circumvent the resistance by combining multi-tyrosine kinase inhibitors lenvatinib (VEGF receptor, fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…58 Golvatinib is an orally bioavailable dual RTKI with potential antiangiogenic activity. 162 It could inhibit the activities of both c-Met and VEGFR-2. Lenvatinib is a multitarget RTKI of VEGFR1-3, FGFR 1-4, PDGFR-, RET, and c-Kit.…”
Section: Multitarget Rtkis As Antiangiogenic Agentsmentioning
confidence: 98%
See 1 more Smart Citation
“…58 Golvatinib is an orally bioavailable dual RTKI with potential antiangiogenic activity. 162 It could inhibit the activities of both c-Met and VEGFR-2. Lenvatinib is a multitarget RTKI of VEGFR1-3, FGFR 1-4, PDGFR-, RET, and c-Kit.…”
Section: Multitarget Rtkis As Antiangiogenic Agentsmentioning
confidence: 98%
“…In addition, it may suppress the activity of VEGFR‐3, c‐MET, and HGF . Golvatinib is an orally bioavailable dual RTKI with potential antiangiogenic activity . It could inhibit the activities of both c‐Met and VEGFR‐2.…”
Section: Recent Advances In Small‐molecule Antiangiogenic Agentsmentioning
confidence: 99%
“…This resistance is overcome by golvatinib (a c-Met inhibitor). 57,58 It is also reported that HGF confers resistance to sunitinib, an inhibitor of multiple kinases, including VEGFR2, by compensating for inhibited angiogenesis. 59,60 Previous studies showed that activity of the c-HGF-Met/Gab1 signaling pathway leads to VEGF production in EGFR-mutant lung cancer cell lines.…”
Section: C-met and Vegfmentioning
confidence: 99%
“…Tie-2 receptor and its ligands, angiopoietins, are also important for angiogenesis. Angiopoietin-2 has been demonstrated as a VEGF negative regulator in several cancers (11,12). In addition to their pro-angiogenic effect, FGF and HGF can also directly promote proliferation, migration and invasion of cancer cells (13,14).…”
Section: Introductionmentioning
confidence: 99%